2004
DOI: 10.1097/01.ju.0000141499.08650.ab
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Aquaporin-7 in Human Testis and Ejaculated Sperm: Possible Involvement in Maintenance of Sperm Quality

Abstract: AQP7 shows a spatial expression pattern in the human testis. AQP7 may be involved in the maintenance of sperm motility. Furthermore, a lack of AQP7 expression in sperm may be an underlying mechanism of male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 18 publications
2
64
0
2
Order By: Relevance
“…The presence of glycerol in the rat epididymis and its metabolism by spermatozoa has been reported [75]. In a study of 22 infertile men, sperm AQP7 was nondetectable in five of them who showed slightly lower sperm motility than the other patients [76]. In a cohort of 50 men, AQP7 expression in ejaculated sperm was correlated with their progressive motility, with low values for both parameters in infertile patients compared with donors [58].…”
Section: Aqp7mentioning
confidence: 97%
“…The presence of glycerol in the rat epididymis and its metabolism by spermatozoa has been reported [75]. In a study of 22 infertile men, sperm AQP7 was nondetectable in five of them who showed slightly lower sperm motility than the other patients [76]. In a cohort of 50 men, AQP7 expression in ejaculated sperm was correlated with their progressive motility, with low values for both parameters in infertile patients compared with donors [58].…”
Section: Aqp7mentioning
confidence: 97%
“…It is well established that the testis expresses AQP7 and AQP8 both at the mRNA and protein levels. AQP7, which was first cloned from the testis (Ishibashi et al 1997), is expressed initially in the round spermatids (Kageyama et al 2001) and is also localised to the sperm tail in the rat (Ishibashi et al 1997, Suzuki-Toyota et al 1999, Kageyama et al 2001, mouse (Skowronski et al 2007) and human (Saito et al 2004). The role of AQP7 in male reproductive physiology is unclear as knockout mice are fertile, producing normal functional spermatozoa , whereas an association with sperm motility has been suggested in infertile men (Saito et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…AQP7, which was first cloned from the testis (Ishibashi et al 1997), is expressed initially in the round spermatids (Kageyama et al 2001) and is also localised to the sperm tail in the rat (Ishibashi et al 1997, Suzuki-Toyota et al 1999, Kageyama et al 2001, mouse (Skowronski et al 2007) and human (Saito et al 2004). The role of AQP7 in male reproductive physiology is unclear as knockout mice are fertile, producing normal functional spermatozoa , whereas an association with sperm motility has been suggested in infertile men (Saito et al 2004). Although there are many studies on AQP8 in the testis, reports on the cellular localisation are inconsistent, ranging from spermatogenic cells in general (Elkjaer et al 2001, Kageyama et al 2001, Yang et al 2005, in elongated spermatids (ES), residual bodies and primary spermatocytes (Calamita et al 2001) and exclusively in Sertoli cells (Badran & Hermo 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hermo and Smith [2011] observed an AQP7 immunoreaction over the whole cytoplasm of late elongating spermatids located near the lumen of rat seminiferous epithelium. AQP7 is expressed in human spermatids and sperm at the tail level [Saito et al 2004;. In human ejaculated sperm, Saito et al [2004] reported immunolabeling in the midpiece region and the anterior portion of the tail, whereas showed the presence of AQP7 along the entire flagellum, with an intensity that varied from cell to cell.…”
Section: Introductionmentioning
confidence: 99%
“…AQP7 is expressed in human spermatids and sperm at the tail level [Saito et al 2004;. In human ejaculated sperm, Saito et al [2004] reported immunolabeling in the midpiece region and the anterior portion of the tail, whereas showed the presence of AQP7 along the entire flagellum, with an intensity that varied from cell to cell. Although this protein seems to play a role in late spermatogenesis and to be involved in mechanisms of male fertility, the function of AQP7 in the male reproductive Figure 1.…”
Section: Introductionmentioning
confidence: 99%